PENGARUH FAKTOR PERSONAL, FAKTOR ORGANISASIONAL, DAN FAKTOR NON ORGANISASIONAL TERHADAP KOMITMEN ORGANISASIONAL KARYAWAN PT AJB BUMI PUTRA GONDOMANAN YOGYAKARTA - Iksan Mulyono; Utik Bidayati (Jurnal Fokus Manajemen Bisnis, 2018)
This study aims to determine the influence of personal factors, factors organizational and non-organizational factors towards organizational commitment employees at PT. AJB Bumi Putera Gondomanan Yogyakarta. This research is a survey research using a questionnaire as the instrument. The population in this study consisted of 40 employees who worked at PT. AJB Bumi Putera Gondomanan Yogyakarta. The sample in this study totaling 40 employees at PT. AJB Bumi Putera Gondomanan Yogyakarta. The population in this study were all employees of PT.AJB Bumi Putera Gondomanan Yogyakarta. Which uses the Sampling method saturation that is taking all the number of employees. The type of data used is primary data. Data is obtained directly from the source or object research is by distributing questionnaires. The results of panel data regression analysis with a significant level of 0.05 can be obtained it was concluded that the 0.173 personal factor hypothesis had no effect on organizational commitment, the second hypothesis of organizational factors 0.296 no effect on organizational commitment, the third hypothesis is non factors organizational 0,008 has a significant effect on organizational commitment, the fourth hypothesis is personal factors, organizational factors and non factors organizational significant effect simultaneously on commitment organizational value of 0.025.